Target Specific Inhibition of Protein Tyrosine Kinase in Conjunction With Cancer and SARS-COV-2 by Olive Nutraceuticals - Arabinda Ghosh; Nobendu Mukerjee; Bhavdeep Sharma; Anushree Pant; Yugal Kishore Mohanta; Rahul D. Jawarkar; Ravindrakumar L. Bakal; Ermias Mergia Terefe; Gaber El-Saber Batiha; Gomaa Mostafa-Hedeab; Gomaa Mostafa-Hedeab; Nisreen Khalid Aref Albezrah; et al. (Frontiers Media S.A., 2022)
Graphical Abstract